Female Executive Leadership, Executive Compensation, and Corporate Governance on Company Performance: A Literature Review - Zainal (Basecamp Economics PubMed, 2024)
This literature review analyzes the relationship between female executive leadership, executive compensation, corporate governance, and company performance. Using a systematic approach, peer-reviewed articles from 2018 to 2023 were gathered from databases focusing on empirical studies, theoretical frameworks, and meta-analyses. The selected studies address how gender diversity in leadership roles, corporate governance structures, and executive compensation practices influence firm performance across different industries and geographic contexts. Findings indicate that female leadership positively impacts managerial ability, decision-making, and financial resilience, especially during economic fluctuations. Additionally, strong corporate governance practices, such as board diversity and effective audit committees, contribute significantly to financial performance indicators like Return on Assets (ROA) and Return on Equity (ROE). This review highlights the crucial role of integrating gender diversity and robust governance in fostering sustainable organizational success.